1992
DOI: 10.1007/bf01462004
|View full text |Cite
|
Sign up to set email alerts
|

Children's reliance on situational and vocal expression of emotions: Consistent and conflicting cues

Abstract: ABSTRACT:The aim of the present study was to investigate developmental differences in reliance on situational versus vocal cues for recognition of emotions. Turkish preschool, second, and fifth grade children participated in the study. Children listened to audiotape recordings of situations between a mother and a child where the emotional cues implied by the context of a vignette and the vocal expression were either consistent or inconsistent. After listening to each vignette, participants were questioned abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
2
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 34 publications
3
25
2
2
Order By: Relevance
“…The age-related increase in emotion-recognition accuracy for both facial and vocal modalities was also consistent with previous findings (Nowicki, 2008;Rosenqvist, Lahti-Nuuttila, Laasonen, & Korkman, 2013;Rothman & Nowicki, 2004). Furthermore, the finding that preschoolers were more accurate at recognizing and labelling angry, compared with happy and sad expressions is largely consistent with previous research (Hortacsu & Ekinci, 1992). The finding that happy vocal expressions were more difficult to recognize compared to angry is also generally consistent with previous research and indicates that, although happiness is more easily recognizable from facial expressions (Ekman, 1994), it is more difficult to identify in vocal expressions (Elfenbein & Ambady, 2002;Scherer, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…The age-related increase in emotion-recognition accuracy for both facial and vocal modalities was also consistent with previous findings (Nowicki, 2008;Rosenqvist, Lahti-Nuuttila, Laasonen, & Korkman, 2013;Rothman & Nowicki, 2004). Furthermore, the finding that preschoolers were more accurate at recognizing and labelling angry, compared with happy and sad expressions is largely consistent with previous research (Hortacsu & Ekinci, 1992). The finding that happy vocal expressions were more difficult to recognize compared to angry is also generally consistent with previous research and indicates that, although happiness is more easily recognizable from facial expressions (Ekman, 1994), it is more difficult to identify in vocal expressions (Elfenbein & Ambady, 2002;Scherer, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…Based on previous studies (Aguert, Laval, Le Bigot, & Bernicot, 2010;Hortaçsu & Ekinci, 1992) revealing that children give priority to situational context over emotional prosody when inferring the emotional states of others, we focused on this issue and broadened the investigation to find out whether the natural combination of emotional prosody and facial expressions (i.e., paralinguistic cues) can overcome the influence of situational context (i.e., extralinguistic cues), and if so, at what age.…”
mentioning
confidence: 99%
“…Studies examining the development of vocal emotion recognition have mainly relied on linguistic stimuli (Baum & Nowicki, 1998;Hortacsu & Ekinci, 1992). While there is some evidence that preschoolers can recognize the speaker's angry, happy, and neutral emotional state (Hortacsu & Ekinci, 1992), further research has found that 4-and 5-year-old children make more errors when asked to recognize sentences with angry, happy, and sad tone of voice compared to 9-and 10-year-old children (McClanahan, 1996;Mitchell, 1995), suggesting that recognition accuracy improves from the preschool years to middle childhood.…”
mentioning
confidence: 99%